2018
DOI: 10.1111/ede.12248
|View full text |Cite
|
Sign up to set email alerts
|

Producing offspring in Armadillidium vulgare: Effects of genetic diversity and inbreeding

Abstract: Genetic diversity is known to be correlated to fitness traits, and inbred individuals often display lower values for life history traits. In this study, we attempt to quantify how inbreeding affects such traits in the terrestrial isopod Armadillidium vulgare by performing inbred and non-inbred crosses under laboratory conditions. We estimated genetic characteristics of parents and offspring, and related them to fecundity and fertility measures, as well as offspring growth and survival. Our study shows that a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…In parallel, the water stress leads to a decrease in reproductive success, as previously reported in females of Antestiopsis thunbergii (Azrag et al, 2017). In A. vulgare, individual body size is positively correlated with fecundity (Durand et al, 2018;Lawlor, 1976), meaning that the slowdown in growth could explain, at least partly, the decrease in reproductive success for stressed animals compared to non-stressed ones. Concerning the water stress, if the loss of moisture has no detectable effect on woodlouse growth, it causes a decrease in both survival and reproductive success.…”
Section: Discussionsupporting
confidence: 73%
“…In parallel, the water stress leads to a decrease in reproductive success, as previously reported in females of Antestiopsis thunbergii (Azrag et al, 2017). In A. vulgare, individual body size is positively correlated with fecundity (Durand et al, 2018;Lawlor, 1976), meaning that the slowdown in growth could explain, at least partly, the decrease in reproductive success for stressed animals compared to non-stressed ones. Concerning the water stress, if the loss of moisture has no detectable effect on woodlouse growth, it causes a decrease in both survival and reproductive success.…”
Section: Discussionsupporting
confidence: 73%
“…Clutch Finally, reproductive senescence can be masked by the selective disappearance of low-quality individuals (Nussey, Coulson, Festa-Bianchet, & Gaillard, 2008). For a given age, larger females produce more offspring in the common woodlouse and body mass is thus generally thought to be a good indicator of individual quality (Durand et al, 2018). We tested for such relationships by modelling the breeding rate as binary data using a generalized linear model (GLM) with maternal mass set as a fixed factor within the young and old mothers separately.…”
Section: Discussionmentioning
confidence: 99%
“…Offspring develop in this pouch and benefit from a protected environment and nutrients provided by their mother (Surbida & Wright, 2001). As the incubation of the offspring takes place in the marsupium, the size of the females is closely associated with the number of offspring produced (Dangerfield & Hassall, 1992; Durand, Loiseau, Prigot, Braquart‐Varnier, & Beltran‐Bech, 2018; Paris & Pitelka, 1962).…”
Section: Methodsmentioning
confidence: 99%
“…In parallel, we observed that the increase in temperature led to a decrease in reproductive success, as previously observed in females of Antestiopsis thunbergii (Azrag et al, 2017). In A. vulgare , the animal size is positively correlated with fecundity (Durand et al, 2018; Lawlor, 1976), meaning that the slowdown in growth could explain, at least partly, the decrease in reproductive success for stressed animals compared to non-stressed ones. Concerning the moisture stress, if the loss of moisture had no detectable effect on woodlouse growth, it caused a decrease in both survival and reproductive success.…”
Section: Discussionmentioning
confidence: 99%